The Impact of Vision 2030 on the Development of Islamic Financial Reporting in Saudi Arabia. Literature Review - Martina Safitry; Reny Fitriana Kaban (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study aims to analyze the impact of this vision on the development of Islamic Financial Reporting in Saudi Arabia through the existing literature review method. Various literature sources are reviewed, including academic journals, government reports, and industry articles to understand how the policies and strategies proposed in the Vision 2030 affect Islamic Financial Reporting and regulations. The analysis results show that the 2030 vision has encouraged increased transparency, technology integration, and adoption of international standards in Islamic Financial Reporting. This initiative has also created an impetus for educational institutions to develop curriculum that are more relevant to changing market needs. In addition, greater interaction between the private sector and regulators is expected to improve Islamic Financial Reporting that are in accordance with Islamic principles and global needs. Overall, Vision 2030 not only contributes to the development of Islamic Financial Reporting in Saudi Arabia but also creates opportunities for sustainable economic growth by making Islamic Financial Reporting an integral part of the modern accounting system.